Performance in a Military Environment: A Qualitative Study of the Effect of Incentives and Rewards on Member Performance in the Scope of Air Squadron 45 - Morin, Natasha Anindika Hermy; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
Work motivation is one of the key factors that affect individual performance in various contexts, including in the military environment. In military organizations, such as the 45th Air Squadron, work motivation not only contributes to operational effectiveness, but also plays an important role in maintaining the morale and discipline of members. This research is a qualitative research. The research sample was 15 (people) who were willing to be interviewed as one of the data collection tools. This research was conducted from November 2024 to January 2025. The main data collection technique was conducted by in-depth and structured interviews with respondents. The incentives and awards received by members in the 45th Air Squadron Scope have a significant impact in improving and driving their performance. By increasing motivation, work quality, satisfaction, and loyalty, incentives and rewards create conditions that support members to deliver better and more optimal performance. Therefore, it is important for management in the 45th Air Squadron to design and implement an effective incentive and reward system to maximize the performance potential of members.